(untitled) (The Review of Diabetic Studies, 2024)
Postoperative infections following dental implant placement represent a significant challenge in restorative dentistry, impacting patient outcomes and the overall success of implant therapy. This comprehensive review aims to elucidate the multifactorial etiology, risk factors, clinical features, diagnostic approaches, management strategies, and preventive measures associated with these infections. The etiology of postoperative infections is often linked to bacterial contamination during surgery, the patient’s oral flora, and systemic health conditions that compromise immune function. Key risk factors include uncontrolled diabetes, smoking, inadequate surgical techniques, and the characteristics of the implant itself, such as surface roughness and bone quality. Clinically, postoperative infections can manifest with localized symptoms, including pain, swelling, and purulent discharge, as well as systemic signs like fever and malaise. The timing of symptom onset can provide insights into the nature of the infection, with early infections typically arising from surgical contamination and late infections often related to peri-implantitis or systemic health issues. Diagnosis primarily relies on clinical evaluation, supported by imaging studies and laboratory tests to identify pathogens and assess the extent of infection. Management strategies encompass conservative approaches, such as antibiotic therapy, and surgical interventions, including drainage and debridement. The decision to remove an implant is made cautiously, weighing the risks of further complications. Prevention of postoperative infections is paramount and involves thorough preoperative assessments, strict adherence to aseptic techniques, and comprehensive patient education regarding postoperative care. In conclusion, understanding the complexities surrounding postoperative infections after dental implant placement is essential for dental professionals. By implementing evidencebased practices and proactive patient management, clinicians can significantly reduce the incidence of infections, thereby enhancing the success rates of dental implants and improving patient satisfaction. Ongoing research and advancements in surgical techniques and materials will continue to inform best practices in this critical area of dental care.